Meteorin-like/Metrnl, a novel secreted protein implicated in inflammation, immunology, and metabolism: A comprehensive review of preclinical and clinical studies - Li, Zhuoqi; Gao, Ziyu; Sun, Tao; Zhang, Shipeng; Yang, Shengnan; Zheng, Meilin; Shen, Hui (Frontiers in Immunology, 2023)
Meteorin-like, also known as Metrnl, Meteorin-β, Subfatin, and Cometin, is a novel secreted protein exerting pleiotropic effects on inflammation, immunology, and metabolism. Earlier research on this hormone focused on regulating energy expenditure and glucose homeostasis. Consequently, several studies attempted to characterize the molecule mechanism of Metrnl in glucose metabolism and obesity-related disorders but reported contradictory clinical results. Recent studies gradually noticed its multiple protective functions in inflammatory immune regulations and cardiometabolic diseases, such as inducing macrophage activation, angiogenesis, tissue remodeling, bone formation, and preventing dyslipidemias. A comprehensive understanding of this novel protein is essential to identify its significance as a potential therapeutic drug or a biomarker of certain diseases. In this review, we present the current knowledge on the physiology of Metrnl and its roles in inflammation, immunology, and metabolism, including animal/cell interventional preclinical studies and human clinical studies. We also describe controversies regarding the data of circulation Metrnl in different disease states to determine its clinical application better.